2001
DOI: 10.1136/sti.77.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Is Mycoplasma hominis a vaginal pathogen?

Abstract: Objective: To evaluate the role of Mycoplasma hominis as a vaginal pathogen. Design: Prospective study comprising detailed history, clinical examination, sexually transmitted infection (STI) and bacterial vaginosis screen, vaginal swabs for mycoplasmas and other organisms, follow up of bacterial vaginosis patients, and analysis of results using SPSS package. (93) with genital warts, 140 (42) chlamydial infections, 54 (29) cases of trichomoniasis, and 249 women with no condition requiring treatment. M hominis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
32
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 9 publications
7
32
2
1
Order By: Relevance
“…This data is also surprising because we expected that Candida should be prevalent in HIV-positive women resulting from a decline of natural immunity due to HIV. In previous studies [16,17] both M. hominis and Ureoplasma have been associated with BV [18], but in our study Ureoplasma was not found in HIVnegative women. This disparity with other studies may be due to the different detection protocols used.…”
Section: Discussioncontrasting
confidence: 50%
“…This data is also surprising because we expected that Candida should be prevalent in HIV-positive women resulting from a decline of natural immunity due to HIV. In previous studies [16,17] both M. hominis and Ureoplasma have been associated with BV [18], but in our study Ureoplasma was not found in HIVnegative women. This disparity with other studies may be due to the different detection protocols used.…”
Section: Discussioncontrasting
confidence: 50%
“…Conversely, relapse of BV after treatment with metronidazole has been attributed to its lack of activity against M. hominis (66), but if the other organisms are eliminated, M. hominis may also disappear. Arya et al (18) found no role for M. hominis in the epidemiology of BV in a study of 341 women who harbored the organism in their vaginas, while Keane and colleagues (141) detected no difference in the occurrence of M. genitalium and Ureaplasma spp. in women with or without BV, but found M. hominis significantly more often in women with BV.…”
Section: Bacterial Vaginosismentioning
confidence: 99%
“…However, the bacterial pathogenesis of PID is unclear in cases where STI microbes are not detected, and where behavioural correlates of PID are not apparent. Many authors mention the role of facultative and anaerobic pathogens [4,5,7 -10], as well as Mycoplasma hominis and Ureaplasma urealyticum [11], as aetiological factors in PID.…”
Section: Introductionmentioning
confidence: 99%